Barium isotope abundances in meteorites and their implications for early Solar System evolution. (15th February 2016) - Bermingham, K.R.; Mezger, K.; Scherer, E.E.; Horan, M.F.; Carlson, R.W.; Upadhyay, D.; Magna, T.; Pack, A.
Abstract: Several nucleosynthetic processes contributed material to the Solar System, but the relative contributions of each process, the timing of their input into the solar nebula, and how well these components were homogenized in the solar nebula remain only partially constrained. The Ba isotope system is particularly useful in addressing these issues because Ba isotopes are synthesized via three nucleosynthetic processes ( s -, r -, p- process). In this study, high precision Ba isotope analyses of 22 different whole rock chondrites and achondrites (carbonaceous chondrites, ordinary chondrites, enstatite chondrites, Martian meteorites, and eucrites) were performed to constrain the distribution of Ba isotopes on the regional scale in the Solar System. A melting method using aerodynamic levitation and CO2 -laser heating was used to oxidize SiC, a primary carrier of Ba among presolar grains in carbonaceous chondrites. Destruction of these grains during the fusion process enabled the complete digestion of these samples. The Ba isotope data presented here are thus the first for which complete dissolution of the bulk meteorite samples was certain. Enstatite chondrites, ordinary chondrites, and all achondrites measured here possess Ba isotope compositions that are not resolved from the terrestrial composition. Barium isotope anomalies are evident in most of the carbonaceous chondrites analyzed, but the 135 Ba anomalies are generally smaller than previously reported for similarly sized splits of CM2 meteorites. Variation in the size of the 135 Ba anomaly is also apparent in fused samples from the same parent body (e.g., CM2 meteorites) and in different pieces from the same meteorite (e.g., Orgueil, CI). Here, we investigate the potential causes of variability in 135 Ba, including the contribution of radiogenic 135 Ba from the decay of 135 Cs and incomplete homogenization of the presolar components on the <0.8 g sample scale.